Social media use and body image issues among adolescents in a vulnerable Louisiana community - Sagrera, Caroline E.; Magner, Johnette; Temple, Jazzlynn; Lawrence, Robert; Magner, Timothy J.; Avila-Quintero, Victor J.; McPherson, Pamela; Alderman, Laura Lane; Bhuiyan, Mohammad Alfrad Nobel; Patterson, James C.; Murnane, Kevin S. (Frontiers in Psychiatry, 2022)
Widespread concern has been expressed regarding unrealistic body image and adolescent eating disorder promoting content on social media (SM) platforms. Numerous research studies have examined the impact of SM on body image as well as social vulnerability on negative mental health outcomes. Despite this, few previous studies have examined the impact of SM on body image specifically in vulnerable, underserved, or predominantly minority communities. This study examines the impact of SM on body image issues (BII) in adolescents in a public school system where greater than 50% of the students live in impoverished households. In late 2019, high school student leaders in Northwest Louisiana developed a survey alongside Step Forward, a collective impact initiative. Questions investigated adolescent SM use and mental health in Caddo Parish, namely BII. Teachers within Caddo Parish Public School System administered the survey. Out of the 11,248 total high school students in the school system, nearly 50% were sampled for a sample size of 5070. Hypotheses included: (1) females were more likely to use SM than males, (2) increasing time spent on SM would correlate with females reporting BII, with males remaining largely unaffected, and (3) highly visual social media (HVSM) platforms would be associated with greater reports of BII than non-HVSM platforms. Results showed females were more likely to use SM (p<0.001) and report BII (p<0.001) compared to males, while both sexes reported BII with increasing time spent on SM (p<0.001). A diversity of platforms were associated with increased BII among SM users compared to non-users (p<0.001): Pinterest, Reddit, Snapchat, TikTok, Twitter, and YouTube. This conclusion is tempered by the omission of race as a variable in the study design, the use of self-report, and the use of an unvalidated instrument. These findings suggest that the harmful association between SM use and BII may transcend culture and socioeconomic status for a broadly deleterious effect on adolescent mental wellbeing.